ANALISIS PENGARUH INSENTIF TERHADAP KINERJA PELAYANAN PUBLIK PADA PEGAWAI RUMAH SAKIT JIWA KENDARI - Muarif Leo leo (Journal of Economic, Public, and Accounting (JEPA), 2020)
performance of public services to the employees of Kendari City Mental Hospital. The design of the study is a quantitative research. The population in this study were employees of the Department of Mental Hospital of Kendari as many as 68 people, using proportionate random sampling using sampling Retrieval of data in the form of interviews and questionnaires. The technique of data analysis using multiple regression models with SPSS 24. The results showed that the incentives consist of material incentives and non-material incentives have a significant effect on the performance of public services in the Department of Mental Hospital of Kendari.